Synthesis and Antibacterial Activities of New 2-Mercapto-Imidazoline-4-one Derivatives - Sahar Abdullah Kadham (Journal of Global Pharma Technology, 2018)
New 2-mercapto-imidazoline-4-one Derivatives comprising 1, 3-thiazoline, Schiff's bases, pyrazole, pyrimidine and γ - lactam moieties are reported. Compound1was synthesized by the reaction of thiourea with Chloro acetyl chloride, compounds 2a - dwere converted into thioester 3a - d Compounds contains pyrazole 5a - h and pyrimidine 6a - hweresynthesized by the reaction of hydrazine hydrate and thiourea with compounds 4a – h respectively Compounds 3a-d and 8a – d were converted into a variety of derivatives. All structural of compounds have been confirmed by FTIR, 1HNMR and mass spectra and tested for invitro antibacterial activity against Escherichia coli, Staphylococcus aurous and Proteus mirabbilisby.Keywords: imidazoline-4-one, 1, 3-thiazoline, Schiff's bases, Pyrazole, Pyrimidine  and γ – lactam.